Sled pushing and pulling to enhance speed capability - Cahill, M.; Cronin, J. B.; Oliver, J. L.; Clark, K.; Cross, M. R.; Llloyd, R. S. (Strength and Conditioning Journal, 2019)
Resisted sprinting in the form of both sled pushing and pulling is a popular training method to improve speed capability, although research has been biased towards investigating the effects of sled pulling. Practitioners need to understand whether the sled push and pull offer differential training effects, and hence their utility in influencing sprint kinematics and kinetics for targeted adaptation. Furthermore, there are a number of recent developments in loading and assessment that warrant discussion, given the impact of these techniques on understanding the load-velocity relationship and optimizing horizontal power output. Finally, some thoughts regarding load prescription are shared with the reader. Abstract from author